Elevated N-Glycosylation Contributes to the Cisplatin Resistance of Non-Small Cell Lung Cancer Cells Revealed by Membrane Proteomic and Glycoproteomic Analysis - Zeng, Wenjuan; Zheng, Shanshan; Mao, Yonghong; Wang, Shisheng; Zhong, Yi; Cao, Wei; Su, Tao; Gong, Meng; Cheng, Jingqiu; Zhang, Yong; Yang, Hao (Frontiers in Pharmacology, 2021)
Chemoresistance is the major restriction on the clinical use of cisplatin. Aberrant changes in protein glycosylation are closely associated with drug resistance. Comprehensive study on the role of protein glycosylation in the development of cisplatin resistance would contribute to precise elucidation of the complicated mechanism of resistance. However, comprehensive characterization of glycosylated proteins remains a big challenge. In this work, we integrated proteomic and N-glycoproteomic workflow to comprehensively characterize the cisplatin resistance-related membrane proteins. Using this method, we found that proteins implicated in cell adhesion, migration, response to drug, and signal transduction were significantly altered in both protein abundance and glycosylation level during the development of cisplatin resistance in the non-small cell lung cancer cell line. Accordingly, the ability of cell migration and invasion was markedly increased in cisplatin-resistant cells, hence intensifying their malignancy. In contrast, the intracellular cisplatin accumulation was significantly reduced in the resistant cells concomitant with the down-regulation of drug uptake channel protein, LRRC8A, and over-expression of drug efflux pump proteins, MRP1 and MRP4. Moreover, the global glycosylation was elevated in the cisplatin-resistant cells. Consequently, inhibition of N-glycosylation reduced cell resistance to cisplatin, whereas promoting the high-mannose or sialylated type of glycosylation enhanced the resistance, suggesting that critical glycosylation type contributes to cisplatin resistance. These results demonstrate the high efficiency of the integrated proteomic and N-glycoproteomic workflow in discovering drug resistance-related targets, and provide new insights into the mechanism of cisplatin resistance.